Building Tolerance from an Early Age: Instilling Religious Moderation Values in Elementary Schools - Mahrus, Mahrus; Afandi, Nur Kholik (LP. Ma'arif Janggan Magetan, 2024)
This study analyzes methods for instilling religious moderation values in public elementary schools to foster tolerance from an early age. Education can introduce students to values of diversity and inclusivity at a young age, as elementary schools serve as a strategic platform to cultivate an understanding of differences. Using a literature review method, data was collected from various relevant sources, including scholarly articles, books, and related documents discussing religious moderation education and tolerance attitudes. Data collection was conducted through literature searches in scientific databases and other credible sources using specific keywords to ensure the relevance of the gathered material. The data was then analyzed descriptively using a thematic analysis approach to identify key themes, such as the integration of religious moderation values into the elementary school curriculum, the role of teachers in guiding students to understand moderate values, the use of extracurricular activities to reinforce tolerance practices, and the creation of an inclusive and diversity-supporting school environment. The study's findings indicate that collaboration among schools, teachers, and parents plays a crucial role in shaping attitudes of tolerance and inclusivity through religious moderation education in elementary schools. The study concludes that instilling religious moderation values at the elementary level is a practical approach to fostering a more peaceful and harmonious society in the future.